If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + -7 = 2(h + 1) Reorder the terms: -7 + 5n = 2(h + 1) Reorder the terms: -7 + 5n = 2(1 + h) -7 + 5n = (1 * 2 + h * 2) -7 + 5n = (2 + 2h) Solving -7 + 5n = 2 + 2h Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 5n = 2 + 7 + 2h Combine like terms: -7 + 7 = 0 0 + 5n = 2 + 7 + 2h 5n = 2 + 7 + 2h Combine like terms: 2 + 7 = 9 5n = 9 + 2h Divide each side by '5'. n = 1.8 + 0.4h Simplifying n = 1.8 + 0.4h
| 5p^2+23p+12=0 | | 8x-3=2(x-1/2) | | 12x^2+5x+3=0 | | 5(x+2)=-30 | | -x^2+5x+3=4 | | 4f-8=4f | | C=[.04(22000)+.5(100)]+.6(1800) | | 18+6(z-3)=5z+4 | | -5(x+7)+117=3x-8(x-5) | | 7m^2-8m=0 | | 450=-650+2.5x | | 3b-12=5b-2 | | 8(b+5)-6=4b+10 | | -6(x-4)-6=30 | | 2(2c-1)-1=2c+5 | | 7n^2-40n+25=0 | | 6x^2+27x+27=0 | | 2x-(2-2x)=2x-1 | | C=765+.6(2000) | | 23-17=3(x-8) | | 8y-14y=-29-37 | | X^2+4x+8=4 | | x+25+2x=0-2x-5 | | -11-5+6n-8=n+6 | | 9x^3y+42x^2y+49xy= | | 16x^2=1024 | | 42-6=8 | | 9x^3u+42x^2y+49xy= | | 60x-12=15 | | -16x-20=-14X+110 | | 7(2x+8)=3(4x-4) | | -18x-5(2x-2)=-21+3 |